2005
DOI: 10.1002/jbm.a.30515
|View full text |Cite
|
Sign up to set email alerts
|

Extensive H+release by bone substitutes affects biocompatibilityin vitrotesting

Abstract: Bone substitutes are widespread in orthopedic and trauma surgery to restore critical bony defects and/or promote local bone healing. Cell culture systems have been used for many years to screen biomaterials for their toxicity and biocompatibility. This study applies a human bone marrow cell culture system to evaluate the toxic in vitro effects of soluble components of different bone substitutes, which are already in clinical use. Different specimens of tricalcium phosphates (TCP) (Vitoss, Cerasorb), nondecalci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
(35 reference statements)
2
12
0
2
Order By: Relevance
“…The collagen nature of this biomaterial greatly influences osteoblastic adherence as demonstrated by Basle et al 2 These authors cultured human osteoblast-like cells (Saos-2) on two different bovine xenogenic biomaterials, which differed in matrix component, the former (Lubboc 1 ) being characterized by preservation of the mineralized collagen matrix and the latter by complete deproteinization, only the mineral phase being preserved; both were reported that the major integrin of the osteoblasts, the b1 subunit known to bind cells and collagen, was localized at the outer surface of osteoblasts in association with collagen bundles of the Lubboc, which attachment being linked to the elongated cells oriented parallel to the collagen bundles while with the deproteinized biomaterial osteoblasts appeared globular and did not adopt any preferential orientation. Our results are in accordance with this study as well as with other studies that reported on the importance of the chemical nature of a bone biomaterial for biointegration of xenogenic implants, 23 in particular, the collagenic nature of the substitute 24,25 for cells migration and proliferation. 25,26 Lubboc biomaterial containing well-integrated oriented collagen bundles as demonstrated at high magnification with electron microscopic studies [see Fig.…”
Section: Discussionsupporting
confidence: 96%
“…The collagen nature of this biomaterial greatly influences osteoblastic adherence as demonstrated by Basle et al 2 These authors cultured human osteoblast-like cells (Saos-2) on two different bovine xenogenic biomaterials, which differed in matrix component, the former (Lubboc 1 ) being characterized by preservation of the mineralized collagen matrix and the latter by complete deproteinization, only the mineral phase being preserved; both were reported that the major integrin of the osteoblasts, the b1 subunit known to bind cells and collagen, was localized at the outer surface of osteoblasts in association with collagen bundles of the Lubboc, which attachment being linked to the elongated cells oriented parallel to the collagen bundles while with the deproteinized biomaterial osteoblasts appeared globular and did not adopt any preferential orientation. Our results are in accordance with this study as well as with other studies that reported on the importance of the chemical nature of a bone biomaterial for biointegration of xenogenic implants, 23 in particular, the collagenic nature of the substitute 24,25 for cells migration and proliferation. 25,26 Lubboc biomaterial containing well-integrated oriented collagen bundles as demonstrated at high magnification with electron microscopic studies [see Fig.…”
Section: Discussionsupporting
confidence: 96%
“…26,27 All volunteer donors had given written consent according to the Declaration of Helsinki in its present form.…”
Section: Cell Culturementioning
confidence: 99%
“…Orthovita], which had shown good cytocompatibility properties in vitro. (15) Twelve hours before xenotransplantation, USSCs were detached from culture flasks supported by 0.05% trypsin/0.02% EDTA and resuspended. A total suspension volume of each 100 l (3 × 10 7 cells/ml) was pipetted onto a 0.5 × 0.5-cm collagen I/III membrane and also onto 10 mg ␤-TCP.…”
Section: Biomaterialsmentioning
confidence: 99%
“…(14,15,46) In addition, several other authors suggest co-administration of growth factors (e.g., BMP-2 or BMP-9) to increase the osteogenic potential of transplanted MSCs.…”
Section: Figmentioning
confidence: 99%